Pengaruh Penambahan Jenis Tepung Yang Berbeda Pada Burger Sapi Terhadap Sifat Fisik, Kimia Dan Organoleptik - Suryaningsih, Lilis; Gumilar, Jajang; Putranto, Wendry Setiyadi; Pratama, Andry; Wulandari, Eka; Utama, Dicky Tri (Jurnal Teknologi Hasil Peternakan, 2024)
Beef Buger is processed chopped meat made in a flat round shape, cooked by steaming. In the process, making beef burgers uses filler and seasonings to add flavor. Using different types of flour as filler can affect the beef burger produced. This research aims to compare different types of flour in beef burgers regarding their physical, chemical and organoleptic properties. This research was carried out using an experimental method using a Completely Randomized Design (CRD) consisting of 3 treatments consisting of T1 = Mocaf Flour, T2 = Tapioca Flour and T3 = Cornstarch with 6 replications, so that 18 experimental units were obtained. The data was processed using test of variance and Duncan's advanced test, while the organoleptic test data was processed using the Kruskal-Wallis and Mann-Whitney advanced tests. The results showed that the use of 10% different types of flour in beef burgers showed significantly different results in all treatments (P<0.05) except for tenderness, and the organoleptic assessment using the best flour as a filler for beef burgers was mocaf flour.